2023
DOI: 10.1002/chem.202203663
|View full text |Cite
|
Sign up to set email alerts
|

C−C and C−N Bond Activation, Lewis‐Base Coordination and One‐ and Two‐Electron Oxidation at a Linear Aminoborylene

Abstract: A cyclic alkyl(amino)carbene (CAAC)‐stabilized dicoordinate aminoborylene is synthesized by the twofold reduction of a [(CAAC)BCl2(TMP)] (TMP=2,6‐tetramethylpiperidyl) precursor. NMR‐spectroscopic, X‐ray crystallographic and computational analyses confirm the cumulenic nature of the central C=B=N moiety. Irradiation of [(CAAC)B(TMP)] (2) resulted in an intramolecular C−C bond activation, leading to a doubly‐fused C10BN heterocycle, while the reaction with acetonitrile resulted in an aryl migration from the CAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The B-N TMP distances of 1.491(2) Å and 1.486(3) Å in 6a and 6c, respectively, are far larger than those reported for typical BQN double bonds, 25,26,38 suggesting single bond character. In contrast, the B-N g distances of 1.367(2) Å and 1.373(2) Å in 6a and 6c, respectively, are comparable with the BQN double bonds in 5 (1.3662(14) Å) 37 and 4b. The N-N bonds in 6a (1.276(2) Å and 1.261(2) Å) and 6c (1.292(3) Å and 1.291(3) Å) are much more equal in length within each complex and can be considered as part of a significantly delocalized N 3 unit.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The B-N TMP distances of 1.491(2) Å and 1.486(3) Å in 6a and 6c, respectively, are far larger than those reported for typical BQN double bonds, 25,26,38 suggesting single bond character. In contrast, the B-N g distances of 1.367(2) Å and 1.373(2) Å in 6a and 6c, respectively, are comparable with the BQN double bonds in 5 (1.3662(14) Å) 37 and 4b. The N-N bonds in 6a (1.276(2) Å and 1.261(2) Å) and 6c (1.292(3) Å and 1.291(3) Å) are much more equal in length within each complex and can be considered as part of a significantly delocalized N 3 unit.…”
mentioning
confidence: 80%
“…In order to extend this study to other borylene species, we employed the stable dicoordinate aminoborylene [(CAAC)B(TMP)] 37 (5) (TMP = 2,6-tetramethylpiperidyl). The low-temperature treatment of aminoborylene 5 with organoazides with different steric and electronic properties, namely phenylazide, 1-azido-4-methoxybenzene, and 1-azido-2,6-dichlorobenzene, afforded compounds 6a-c in 71%, 73% and 97% yields, respectively, as red solids (Scheme 1(ii)).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such dimerization reactions (let alone equilibria) are as of yet unknown for the lightest group 13 analogues, dicoordinate borylenes, and their formal diborene dimers, which, unlike their heavier group 13 analogues, are planar. Following Bertrand’s and Robinson’s landmark syntheses of the first metal-free borylene and diborene, respectively, , the past decade has seen a surge in the reports of doubly base-stabilized tricoordinate LL′(R)­B: borylenes and L­(R)­BB­(R)­L diborenes. Stable L­(R)­B: dicoordinate borylenes, however, remain limited to a few examples stabilized by the push–pull interaction of a π-donating amino substituent and a π-accepting carbene ligand ( I , Scheme a). Due to the linear geometry, steric shielding, and electronic saturation of their boron center, these species do not dimerize to the corresponding diaminodiborenes. Thus far, attempts to generate dicoordinate borylenes in situ by the photolytic or thermal abstraction of a labile donor ligand (e.g., CO, PMe 3 ) from a tricoordinate borylene have systematically led to intramolecular C–H or C–C activation reactions rather than dimerization. Experimental and computational studies on the only known formal borylene-diborene L­(R)­B:/L­(R)­BB­(R)­L pair, tetrameric cyanoborylene I and cyanodiborene II (Scheme a), showed that these two species do not interconvert owing to the preferred self-stabilization of I through B–CN–B linkages. , The fact, however, that certain LBRX 2 (X = halide) precursors can be reduced either to a tricoordinate borylene (or borylene equivalent) in the presence of a second base L′ or to a diborene in the absence thereof suggests the feasibility of borylene-to-diborene dimerization.…”
Section: Introductionmentioning
confidence: 99%